Motivational trip to UiTM Pahang: a study of students' academic motivation and interest - Mustapha, Musramaini; Baharum, Norzie Diana (Universiti Teknologi MARA, 2009)
For decades, schools have been playing their big role in providing education for Malaysians. School is the place where intellectual mind is formally founded and social skills are cemented. Being education providers, it is expected that schools would be the place where students derive their academic motivation, the realm that would make available any educational information inclusive of information related to tertiary education institutions such as universities and colleges. Although the role played by school teachers or counselors in providing this university-related information is undoubtedly important, the information provided is mostly given in general, thus, making it insufficient for students. With this Limitation, should schools be Left to single-handedly provide all the necessary knowledge about tertiary education and institutions? Should school teachers and counselors, too, be working alone in motivating secondary school students? What can a higher institution itself do to closely reach the potential students and then enhance their academic aspiration? This study, therefore, attempts to look at how UiTM Pahang, through its academic motivational trip, can help boost Local secondary students' academic motivation as well as assist them in paving a path towards tertiary excellence.